The presence of Toxoplasma gondii in soil, their transmission, and their influence on the small ruminants and human population: A review. (September 2021) - Kakakhel, Mian Adnan; Wu, Fasi; Anwar, Zahid; Saif, Irfan; Akbar, Noor ul; Gul, Naila; Ali, Ihsan; Feng, Huyuan; Wang, Wanfu
Abstract: The ecosystem approach has been developed since the 1940s. An ecosystem is a community of living organism and their interaction and conjugation with abiotic factors of the environment. The ecosystem is not endemic to the aquatic environment only but, the terrestrial environment is also considered to be a part of an ecosystem. Soil act as mother role for the survival of different microorganism. The Toxoplasma gondii oocysts stay survive for a long time in the soil. This presence of these oocysts might critically enhance the success of this parasite in two ways. First, this parasite can widespread; second, it can create a lot of consequences regarding animals and their economic value. Soil contamination caused by Toxoplasma gondii Y is a significant and profound issue for animals and public health. Therefore, the current study was aimed to summarize and correlate the soil and parasite, their transmission, infection, and some aspects related to T. gondii . The small animals are pose at a high risk therefore, it was concluded that some preventive measures should be taken to keep secure itself from zoonotic diseases. Graphical abstract: Image 1 Highlights: An ecosystem is a community of living organism and their interaction and conjugation with abiotic factors of the environment. Soil ecosystem plays an important role in the maintenance of ecosystems and human activities. Soil contamination by the parasite is the most prominent and significant risk factor for humans and animals. Oocysts of Toxoplasma gondii present in soil for a long time. Avoiding undercook meat consumption can reduce the chances of toxoplasma infection.